Acute Traumatic Aortic Injury. Issue 3 (May 2015) - Raptis, Constantine A.; Hammer, Mark M.; Raman, Kathleen G.; Mellnick, Vincent M.; Bhalla, Sanjeev
<x xml:space="preserve">Abstract</x> The diagnosis of acute traumatic aortic injury (ATAI) relies heavily on accurate and efficient imaging interpretation, thereby making the radiologist integral to the care of patients in whom these life-threatening lesions are suspected. Typically, this evaluation begins with the initial trauma radiograph, in which findings suggestive of mediastinal hematoma or ATAI can be detected. Definitive diagnosis of ATAI is made with the current gold standard, computed tomography, wherein indirect and direct signs of ATAI provide the means for sensitive and specific diagnosis. Although the diagnosis of ATAI on computed tomography can be straightforward, technical and anatomic pitfalls can complicate interpretation and must be understood. Once the diagnosis is made, the radiologist needs to provide a meaningful report that includes an appropriate description of the lesion location and characteristics. The purpose of this article is to review the key aspects of the imaging evaluation of ATAI with a focus on factors that affect the management of these patients.